PENGARUH KECERDASAN EMOSIONAL, TINGKAT PENDIDIKAN DAN KARIR TERHADAP KINERJA KARYAWAN (Studi kasus pada Sales Marketing PT Astra International Daihatsu Cabang Tangerang) - Widayati, Catur (Jurnal Ekonomi, 2016)
This study aims to determine the effect of Emotional Intelligence, Education and  Career  Levels  Of  Performance  (sales  marketing  case  study  on  PT  Astra International Daihatsu Branch Tangerang) using a descriptive approach Kuantitatif Sampel this peneliian employee sales force in PT Astra International Daihatsu Branch Tangerang. Using the questionnaire and SPSS analysis. These results indicate that the EQ variable has a positive and significant impact on employee performance variable partial  test  results  (test  T),  0.021  <0.05,  Pendididkan  rate  does  not  affect  the performance of employees with a partial test (t test) 0.452> 0.05 and career do not affect the performance of employees with a partial test (t test) 0.095> 0.05.